Family History of Alzheimer's Disease and Subjective Memory Performance. Issue 7 (November 2018) - Haussmann, Robert; Ganske, Steffi; Gruschwitz, Antonia; Werner, Annett; Osterrath, Antje; Lange, Jan; Buthut, Maria; Donix, Katharina L.; Linn, Jennifer; Donix, Markus
People with a first-degree family history of Alzheimer's disease are at an increased risk of developing dementia. Subjective memory impairment among individuals with no measurable cognitive deficits may also indicate elevated dementia risk. It remains unclear whether nondemented people with a positive family history of Alzheimer's disease are more likely to experience cognitive deficits and whether such an association reflects underlying neuropathology. We therefore investigated subjective memory impairment and hippocampal cortical thickness in 40 healthy older adults and 35 patients with amnestic mild cognitive impairment. We found greater subjective memory impairment and left hemispheric hippocampal cortical thinning associated with a first-degree family history of Alzheimer's disease in healthy older adults. This suggests that subjective memory impairment could reflect preclinical stage neurodegeneration among individuals with the family history risk factor.